Reactive silicone composition and cured product thereof
By using reactive organosilicon compounds with specific structures and modified oxide colloidal particle compositions containing titanium oxide, the problems of insufficient transparency and poor heat resistance of optical adhesives and optical waveguides in the photoelectric composite substrate are solved, and cured products with high refractive index, excellent light resistance and low light loss are achieved, and are suitable for optical signal transmission devices.
Patent Information
- Application Number
- CN201980076624.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-21
- Filing Date
- 2019-11-01
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-11-01
AI Technical Summary
In the photoelectric composite substrate, the existing optical adhesives and optical waveguides are insufficient in the near-infrared light region, resulting in high light loss and difficult control of heat resistance and refractive index, which affects the sealing and connection accuracy of the optical wiring.
A composition containing a reactive silicone compound with a specific structure and a modified oxide colloidal particles containing titanium oxide is used to form a cured product with high refractive index, excellent light resistance and heat resistance through condensation reaction and surface modification techniques.
It realizes a material with excellent transparency and low propagation loss in the near-infrared light region, has good processability and curability, and is suitable for the connection of optical waveguides and fixing of light-receiving and light-emitting elements in optical signal transmission devices.
Smart Images

Figure CN113166343B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a reactive silicone composition that can produce a cured product having excellent transparency and a high refractive index. The reactive silicone composition is useful as an optical wiring material such as an optical adhesive or a transparent sealant, or an on-board optical interconnect, such as a core member in an optical signal transmission device. Background Art
[0002] In recent years, the amount of communication information has been increasing due to the development of cloud computing and the increase in the number of smartphone users. As a result, the data servers that collect the information data sent have been experiencing huge power usage and the limit of further processing capacity has been approaching. The development of technologies to improve these problems has become a top priority.
[0003] Under such circumstances, as a technology capable of processing information at high density and speed, a technology such as an optoelectronic composite board (also called an optoelectronic hybrid board) in which a part of the electrical wiring in a server motherboard is replaced with optical wiring is being vigorously studied.
[0004] In an optoelectronic composite substrate, the light-receiving and light-emitting elements that transmit and receive signals via an optical waveguide as an optical transmission path are sealed with a transparent optical adhesive to improve the reliability of the elements. For example, an optical adhesive is used to connect a light-receiving and light-emitting element such as a vertical surface emitting laser element (VCSEL) to an optical waveguide on a substrate, and then soldering is performed by reflow to connect the electrical wiring to the light-receiving and light-emitting element and fix the element.
[0005] The optical adhesive and optical waveguide used here are required to be transparent at near-infrared wavelengths such as 850nm, 1.31μm, and 1.55μm used in optical communications. In addition, in order to reduce the light loss in the connection part caused by the refractive index difference between the optical waveguide or the light-receiving and light-emitting element and the optical adhesive, it is desired that the refractive index of the optical material used in the optical adhesive, optical waveguide, etc. can be controlled.
[0006] In addition, for optoelectronic composite boards, the use of high-strength lead-free solder is being studied in order to firmly fix the light-receiving and light-emitting elements to the board. The reflow of lead-free solder requires high temperatures, so a high temperature of 280°C may be applied to the printed wiring board. Therefore, high heat resistance is required for optical wiring-related materials (optical waveguides, optical adhesives) used in optoelectronic composite boards.
[0007] As optical adhesives having excellent transparency and heat resistance, curable resin compositions characterized by containing an adamantane derivative having a specific structure (Patent Document 1) and curable resin compositions characterized by containing a (meth)acrylate having an alicyclic hydrocarbon group (Patent Document 2) have been proposed.
[0008] Furthermore, a vinyl-based organic silicon compound has been proposed as a material capable of forming an optical waveguide having transparency and heat resistance in the near-infrared wavelength region (Patent Document 3).
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2010-132576
[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 11-61081
[0013] Patent Document 3: Japanese Patent Application No. 2014-510159 Summary of the invention
[0014] Problems to be solved by the invention
[0015] In the process of studying the practical application of optoelectronic composite substrates, optical materials such as optical adhesives and optical waveguides used in these substrates are required to have low propagation loss in the long wavelength region, heat resistance, and adjustable refractive index. In addition, these materials are required to have good precision in forming optical wiring on the above-mentioned substrates, and to have excellent processability that can be achieved by simple and universal means.
[0016] The present invention is proposed in view of such circumstances, and its purpose is to provide a reactive silicone composition that is transparent in the near-infrared light region used in optical communications, has an adjustable refractive index, can easily form a microstructure using conventional semiconductor processing techniques such as photolithography and etching, and has excellent light resistance and heat resistance after curing.
[0017] Methods for solving problems
[0018] In order to solve the above-mentioned problems, the present inventors conducted intensive research and found that a reactive silicone composition comprising a reactive silicone compound of a specific structure and colloidal particles containing titanium oxide of a specific structure whose surface is modified with the silicone compound can obtain a cured product having excellent transparency, adjustable refractive index, and excellent light resistance, and also has excellent processability that allows the cured product to be easily formed by light irradiation and heating, thereby completing the present invention.
[0019] That is, the present invention, as a first aspect, relates to a reactive silicone composition comprising the following components (S) and (T),
[0020] The component (S) is a reactive organic silicon compound composed of a condensation product of a diarylsilicic acid compound represented by formula [1] and a silicon compound represented by formula [2].
[0021]
[0022] (Where Ar 1 and Ar 2 Each independently represents a phenyl group which may optionally have an alkyl group having 1 to 6 carbon atoms as a substituent, and X represents a hydrolyzable reactive group.
[0023] The above-mentioned (T) component is a modified titanium oxide-containing colloidal particle formed by bonding an organic silicon compound to the surface of titanium oxide-containing oxide colloidal particles (C) having an average particle size of 2 to 100 nm, wherein the above-mentioned titanium oxide-containing oxide colloidal particles (C) have titanium oxide-containing metal oxide colloidal particles (A) having an average primary particle size of 2 to 60 nm as a core, and the core surface is coated with a coating formed by colloidal particles (B) of a composite oxide containing silicon dioxide and tin oxide having an average primary particle size of 1 to 4 nm.
[0024] As a second aspect, the present invention relates to the reactive silicone composition according to the first aspect, comprising cyclohexanone or 2-butanone as a solvent.
[0025] As a third aspect, the present invention relates to the reactive silicone composition according to the first aspect or the second aspect, further comprising a polymerization initiator.
[0026] As a fourth aspect, the present invention relates to a cured product formed from the reactive silicone composition according to any one of the first aspect to the third aspect.
[0027] As a fifth aspect, the present invention relates to an optical adhesive formed from the reactive silicone composition according to any one of the first to third aspects and used for a connection between optical waveguides or between an optical waveguide and a light receiving element in an optical signal transmission device.
[0028] As a sixth aspect, the present invention relates to a core member in an optical signal transmission device, the core member being formed of the cured product according to the fourth aspect.
[0029] As a seventh aspect, the present invention relates to a film-forming agent formed from the reactive silicone composition according to any one of the first aspect to the third aspect.
[0030] As an eighth aspect, the present invention relates to an optical member having a cured film formed from the reactive silicone composition according to any one of the first aspect to the third aspect on a surface of an optical substrate.
[0031] As a ninth aspect, the present invention relates to an optical member, characterized in that an antireflection film is further applied to the surface of the optical member according to the eighth aspect.
[0032] Effects of the Invention
[0033] According to the present invention, in a reactive organosilicon composition obtained by combining a reactive organosilicon compound of a specific structure and colloidal particles containing titanium oxide of a specific structure whose surface is modified with the organosilicon compound, a cured product having a high refractive index and excellent light resistance can be formed. In addition, by adjusting the mixing ratio of the reactive organosilicon compound and the colloidal particles containing titanium oxide and the composition of the colloidal particles containing titanium oxide in the reactive organosilicon composition, the refractive index of the obtained cured product can be adjusted.
[0034] Furthermore, since the cured product of the reactive silicone composition according to the present invention has excellent transparency in the near-infrared region, it is possible to provide a material having low propagation loss in the long wavelength region.
[0035] The reactive silicone composition of the present invention can easily form a cured product by light irradiation or heating, and can also be used in the form of a varnish. It can also easily form a thin film and can be used as a coating composition. Therefore, the reactive silicone composition of the present invention can form a cured film (coating layer) with excellent transparency, high refractive index, and excellent light resistance.
[0036] Furthermore, the reactive silicone composition according to the present invention can provide a composition which suppresses aggregation, precipitation and precipitate even after long-term storage and has excellent storage stability, and can also be provided as a coating material with high stability.
[0037] Furthermore, the cured product obtained from the reactive organic silicone composition of the present invention has excellent transparency in the near-infrared light region, a high refractive index, and light resistance, and the refractive index can be easily adjusted by adjusting the blending amount of the reactive organic silicone compound and the colloidal particles and the composition of the colloidal particles.
[0038] Therefore, the cured product of the present invention is useful in improving the reliability of optical devices used in optoelectronic composite substrates, and is particularly useful as an optical adhesive used for connecting optical waveguides in optical signal transmission devices, connecting optical waveguides and light-receiving and light-emitting elements, and as a core component in optical signal transmission devices (such as cables).
[0039] In addition, when the above-mentioned cured product is formed in the form of a film (layer) on the surface of an optical substrate to make an optical component, the optical component has excellent transparency, a high refractive index, and excellent light resistance. In addition, even when a high refractive index component with a refractive index of more than 1.58 is used, an optical component with high transparency and good appearance in which no interference fringes are seen can be obtained.
[0040] Therefore, the optical member having a cured film produced from the reactive silicone composition of the present invention can be used for, in addition to eyeglass lenses, camera lenses, automobile window glass, optical filters attached to liquid crystal displays, plasma displays, and the like. DETAILED DESCRIPTION
[0041] [Reactive silicone composition]
[0042] The reactive silicone composition of the present invention comprises a reactive silicone compound as component (S) and modified oxide colloidal particles containing titanium oxide as component (T), and may contain a solvent, a polymerization initiator, and a reactive diluent as described below.
[0043] Hereinafter, each component constituting the reactive silicone composition of the present invention will be described in detail.
[0044] 《(S) ingredient》
[0045] The component (S) of the present invention is a reactive organic silicon compound obtained by polycondensing a diarylsilicic acid compound represented by formula [1] and a silicon compound represented by formula [2] in the presence of an acid or a base, that is, a condensation product of a diarylsilicic acid compound represented by formula [1] and a silicon compound represented by formula [2], and as an example, a dealcoholization condensation product can be mentioned.
[0046] <Diarylsilicic acid compound represented by formula [1]>
[0047] Examples of the diarylsilicic acid compound used in the present invention include compounds represented by the following formula [1] (hereinafter, also simply referred to as compounds of the formula [1]).
[0048]
[0049] In the formula, Ar 1 and Ar 2 Each independently represents a phenyl group which may have an alkyl group having 1 to 6 carbon atoms as a substituent. 1 and Ar 2 Examples of the group include phenyl, 2-methylphenyl, 3-methylphenyl, 4-ethylphenyl, and 4-isopropylphenyl.
[0050] Specific examples of the compound represented by the above formula [1] include diphenylsilanediol, di(4-methylphenyl)silanediol, di(4-ethylphenyl)silanediol, di(4-isopropylphenyl)silanediol, and the like, but are not limited thereto.
[0051] The compound represented by the above formula [1] may be used alone or as a mixture of two or more.
[0052] <Silicon compounds>
[0053] Examples of the silicon compound used in the present invention include compounds represented by the following formula [2] (hereinafter, also simply referred to as compounds of the formula [2]).
[0054]
[0055] In the formula, X represents a hydrolyzable reactive group (a group that can undergo a hydrolyzable condensation reaction).
[0056] X preferably represents an alkoxy group having 1 to 10 carbon atoms, an acyloxy group having 2 to 5 carbon atoms, an alkylcarbonyl group having 2 to 6 carbon atoms, an alkoxycarbonyl group having 2 to 6 carbon atoms, or a NR group. 1 2(where R 1 More preferably, X represents an alkoxy group having 1 to 6 carbon atoms, for example, a methoxy group or an ethoxy group.
[0057] Specific examples of the compound represented by formula [2] include 4-vinylphenyltrimethoxysilane (p-phenylvinyltrimethoxysilane) and 4-vinylphenyltriethoxysilane (p-phenylvinyltriethoxysilane), but are not limited thereto.
[0058] The compound represented by the above formula [2] may be used alone or as a mixture of two or more.
[0059] <Blending ratio of diarylsilicic acid compound and silicon compound>
[0060] The mixing ratio of the diarylsilicic acid compound [1] and the silicon compound [2] used in the preparation of the above-mentioned reactive organosilicon compound is not particularly limited. For example, from the purpose of preventing block copolymerization, the compound of formula [1]: the compound of formula [2] can be mixed in a molar ratio of 2:1 to 1:2. These compounds are more preferably mixed in a molar ratio of 1.1:0.9 to 0.9:1.1, for example, they can be mixed in a molar ratio of about 1:1. In addition, for the purpose of ensuring that there are no free hydroxyl groups in the reactive organosilicon compound, it is preferably mixed in a molar ratio of about 1:1 to 0.9:1.1, for example.
[0061] The diarylsilicic acid compound represented by the formula [1] and the silicon compound represented by the formula [2] can be appropriately selected and used as described above, and the compound of the formula [1] and the compound of the formula [2] can be used alone or in combination of two or more thereof. When using two or more thereof in combination, they can be mixed so that the total molar number of the compound of the formula [1] and the total molar number of the compound of the formula [2] are within the above numerical ranges.
[0062] <Reactive organosilicon compounds: polycondensation reaction>
[0063] One of the characteristics of the reactive organic silicon compound (condensation product) used in the present invention, which is obtained by polycondensing a diarylsilicic acid compound represented by the above formula [1] and a silicon compound represented by the above formula [2] in the presence of an acid or a base, is the structure of the silicon compound represented by the above formula [2]. The reactive group (polymerizable double bond) contained in the compound of the formula [2] is easily polymerized by free radicals, and exhibits high heat resistance after polymerization (after curing).
[0064] Generally, when a silicon compound represented by formula [2] is subjected to polycondensation together with a diarylsilicic acid compound represented by formula [1] to obtain a reactive organosilicon compound having high heat resistance, the reaction needs to be stopped at an appropriate degree of polymerization in order to keep the product in a liquid state. In the embodiment in which the silicon compound represented by formula [2] used in the present invention is an alkoxysilicic acid compound, the polycondensation reaction with the diarylsilicic acid compound is smooth, so it is easy to control the degree of polymerization, which can be said to be an advantage of this embodiment.
[0065] The polycondensation reaction between the silicon compound represented by formula [2], preferably an alkoxysilicon compound, and the diarylsilicic acid compound represented by formula [1] by dealcoholization or the like can be carried out in the absence of a solvent, but a solvent inactive to the compound represented by formula [2] (e.g., toluene) can also be used as a reaction solvent.
[0066] Furthermore, when the polycondensation reaction is carried out in the absence of a solvent and the compound represented by the formula [2] is an alkoxysilicon compound, there is an advantage that alcohol produced as a reaction by-product can be easily removed by distillation.
[0067] On the other hand, when a reaction solvent is used, there is an advantage that the reaction system can be easily made uniform, and a more stable polycondensation reaction can be performed.
[0068] <Solvent used for polycondensation reaction>
[0069] The synthesis (polycondensation) reaction of the reactive organosilicon compound can be carried out without a solvent as described above, but a solvent may be used to make the reaction more uniform. The solvent is not particularly limited as long as it does not react with the diarylsilicic acid compound and the silicon compound and does not dissolve their polycondensate.
[0070] Examples of the solvent include ketones such as acetone and 2-butanone, aromatic hydrocarbons such as benzene, toluene, and xylene, glycols such as ethylene glycol, propylene glycol, and hexylene glycol, glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, and diethyl carbitol, N-methyl-2-pyrrolidone, N,N-dimethylformamide, esters such as ethyl acetate, and alcohols such as methanol or ethanol in the following cases. Alcohols are suitable when X in formula [2] is a group other than an alkoxy group, and in this case, the alcohols can be used to control the polycondensation reaction by re-esterification.
[0071] When a solvent is used for the polycondensation reaction, particularly preferred solvents include toluene, xylene and 2-butanone.
[0072] The above solvents may be used alone or in combination of two or more.
[0073] <Other catalysts, etc.>
[0074] A catalyst can be used in the polycondensation reaction. As the catalyst that can be used, as long as it is dissolved or uniformly dispersed in the above-mentioned solvent, its type is not particularly limited, and can be appropriately selected and used as needed. The catalyst can be used alone or in combination of multiple types.
[0075] Examples of catalysts that can be used include acidic compounds such as Ti(OR)4, Zr(OR)4, B(OR)3 and Al(OR)3, alkaline compounds such as alkaline earth metal hydroxides, and fluoride salts such as NH4F and NR4F (where R is one or more groups selected from a straight-chain hydrocarbon group having 1 to 12 carbon atoms, a branched-chain alkyl group having 3 to 12 carbon atoms and a cyclic alkyl group having 3 to 12 carbon atoms).
[0076] Specific examples of the acidic compound include trimethoxyaluminum, triethoxyaluminum, tri-n-propoxyaluminum, triisopropoxyaluminum, tri-n-butoxyaluminum, triisobutoxyaluminum, tri-sec-butoxyaluminum, tri-tert-butoxyaluminum, trimethoxyboron, triethoxyboron, tri-n-propoxyboron, triisopropoxyboron, tri-n-butoxyboron, triisobutoxyboron, tri-sec-butoxyboron, tetramethoxytitanium, tetraethoxytitanium, tetra-n-propoxytitanium, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetraisobutoxytitanium, tetra-sec-butoxytitanium, tetra-tert-butoxytitanium, tetramethoxyzirconium, tetraethoxyzirconium, tetra-n-propoxyzirconium, tetraisopropoxyzirconium, tetra-n-butoxyzirconium, tetraisobutoxyzirconium, tetra-sec-butoxyzirconium, and tetra-tert-butoxyzirconium.
[0077] Examples of the basic compound include barium hydroxide, sodium hydroxide, potassium hydroxide, strontium hydroxide, calcium hydroxide, magnesium hydroxide, ammonium hydroxide, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, and triethylamine.
[0078] Examples of the fluoride salt include ammonium fluoride, tetramethylammonium fluoride, tetrabutylammonium fluoride, and the like.
[0079] Among these catalysts, preferably used is one or more compounds selected from the group consisting of tetraisopropoxytitanium (titanium isopropoxide), barium hydroxide, strontium hydroxide, calcium hydroxide, and magnesium hydroxide.
[0080] When a catalyst is used, the amount used is 0.01% by mass or more, for example 0.01 to 10% by mass, or 0.1 to 5% by mass, relative to the total mass of the diarylsilicic acid compound represented by formula [1] and the silicon compound (preferably an alkoxysilicon compound) represented by formula [2], from the viewpoint of its action as a catalyst (progress of the reaction).
[0081] <Reaction conditions for condensation reaction> The reactive organosilicon compound used in the present invention is obtained by subjecting a diarylsilicic acid compound represented by formula [1] and a silicon compound represented by formula [2] to a polycondensation reaction such as dealcoholization condensation in the presence of an acid or alkaline catalyst. In a preferred embodiment, the polycondensation reaction is carried out without adding water, for example, the water that may be mixed in through the surroundings (reagent, glass wall, atmosphere above the material) can be suppressed as much as possible, and the reaction can be carried out in the absence of water (without adding water). For such reasons, the reaction can be carried out in an inert gas atmosphere such as nitrogen, and the reaction container can be heated before use. Furthermore, in order to prevent the mixing of water, an anhydrous reagent can be used.
[0082] The reaction temperature can be selected as needed, for example, in the range of 20°C to 150°C, or in the range of 30°C to 120°C.
[0083] The reaction time is not particularly limited as long as it is equal to or longer than the time required for the molecular weight of the polycondensate to be completely increased and for the molecular weight distribution to be stabilized, and is, for example, several hours to several days.
[0084] When the silicon compound represented by the formula [2] is an alkoxysilicon compound, the reaction system may distill off the alcohol produced as a by-product under reduced pressure during the reaction in order to promote dealcoholization condensation. However, distillation of the alcohol is not essential.
[0085] 《(T) ingredient》
[0086] The component (T) contained in the reactive silicone composition of the present invention is modified titanium oxide-containing colloid particles having an organosilicon compound bonded to the surface thereof.
[0087] More specifically, the component (T) is a modified titanium oxide-containing colloid particle formed by bonding an organosilicon compound to the surface of a titanium oxide-containing colloid particle (C) having an average particle size of 2 to 100 nm. The colloid particle (C) is a colloid particle having a core of a titanium oxide-containing metal oxide colloid particle (A) having an average primary particle size of 2 to 60 nm, and the core surface is coated with a coating formed of a composite oxide containing silicon dioxide and tin oxide and having an average primary particle size of 1 to 4 nm.
[0088] In the present invention, the average primary particle size of the colloidal particles (A) of the metal oxide containing titanium oxide as the core and the colloidal particles (B) of the composite oxide as the coating is measured by observation using a transmission electron microscope. The average particle size of the colloidal particles (C) of the oxide containing titanium oxide, the surface of which is coated with the coating formed by the particles (B), can be measured by a dynamic light scattering method (DLS method).
[0089] In addition, when the surface of the above-mentioned metal oxide colloidal particles (A) containing titanium oxide is coated with the above-mentioned composite oxide colloidal particles (B), the value of the particle size of the obtained oxide colloidal particles (C) containing titanium oxide may change according to the reaction between the interfaces of the particles. Therefore, when the particle size of the oxide colloidal particles (C) containing titanium oxide is measured by observation using a transmission electron microscope and evaluated by the primary particle size, this value may not necessarily coincide with the sum of the average primary particle sizes of the above-mentioned metal oxide colloidal particles (A) containing titanium oxide and the above-mentioned composite oxide colloidal particles (B).
[0090] Hereinafter, in this specification, the particle size measured by transmission electron microscope observation is referred to as “average primary particle size”, and the particle size measured by dynamic light scattering (DLS) is referred to as “average particle size (dynamic light scattering particle size)”.
[0091] <Metal oxide colloidal particles containing titanium oxide (A)>
[0092] The titanium oxide-containing metal oxide colloidal particles (A) are particles having an average primary particle size of 2 to 60 nm.
[0093] The titanium oxide-containing metal oxide colloidal particles (A) may be composed of titanium oxide alone, or may contain titanium oxide and components other than titanium oxide.
[0094] As components other than titanium oxide, for example, oxides of at least one metal selected from Fe, Cu, Zn, Y, Zr, Nb, Mo, In, Sn, Sb, Ta, W, Pb, Bi and Ce can be cited. As the form of these metal oxides, for example, Fe2O3, CuO, ZnO, Y2O3, ZrO2, Nb2O5, MoO3, In2O3, SnO2, Sb2O5, Ta2O5, WO3, PbO, Bi2O3, CeO2, etc. can be exemplified. These metal oxides can be used alone or in combination.
[0095] When the above-mentioned colloidal particles (A) contain titanium oxide and components other than titanium oxide (metal oxides), as a combination method, there can be cited a method of mixing the above-mentioned titanium oxide with one or more metal oxides, a method of composite the above-mentioned titanium oxide with one or more metal oxides, or a method of forming a solid solution of the above-mentioned titanium oxide with one or more metal oxides at the atomic level.
[0096] As specific examples of the case where the above-mentioned colloidal particles (A) contain components (metal oxides) other than titanium oxide, there can be cited TiO2-SnO2 composite metal oxide colloidal particles in which TiO2 particles and SnO2 particles are composited by chemical bonds at their interfaces, TiO2-SnO2-ZrO2 composite metal oxide colloidal particles in which TiO2, SnO2 and ZrO2 form a solid solution at the atomic level, etc.
[0097] In addition, the colloidal particles (A) may be amorphous or may be crystals of anatase, rutile, brookite, etc. Further, they may be perovskite-type titanium compounds such as barium titanate (represented by BaTiO3 or BaO·TiO2). Among them, the crystal form of the metal oxide colloidal particles containing titanium oxide is preferably rutile.
[0098] The titanium oxide content in the above-mentioned metal oxide colloidal particles (A) containing titanium oxide is 40 to 100% by mass in terms of TiO2, preferably 50% by mass or more, and more preferably 70% by mass or more. By making the titanium oxide content 50% by mass or more, it is expected that the refractive index of the cured product (cured film, transparent film, etc.) obtained by using the composition containing these particles can be improved, and in addition, the generation of interference fringes that may occur due to the refractive index of the substrate can be suppressed.
[0099] In addition, the metal oxide colloidal particles (A) containing titanium oxide can be produced by known methods, such as ion exchange method, peptization method, hydrolysis method, and reaction method. As an example of the above-mentioned ion exchange method, there can be mentioned a method of treating the acidic salt of the above-mentioned metal (Ti, metal other than Ti) with a hydrogen-type ion exchange resin, or a method of treating the basic salt of the above-mentioned metal (Ti, metal other than Ti) with a hydroxyl-type anion exchange resin. As an example of the above-mentioned peptization method, there can be mentioned a method of washing the gel obtained by neutralizing the acidic salt of the above-mentioned metal with a base, or neutralizing the basic salt of the above-mentioned metal with an acid, and then peptizing with an acid or a base. As an example of the above-mentioned hydrolysis method, there can be mentioned a method of hydrolyzing the alcohol salt of the above-mentioned metal, or a method of removing the unnecessary acid after hydrolyzing the basic salt of the above-mentioned metal under heating. As an example of the above-mentioned reaction method, there can be mentioned a method of reacting the powder of the above-mentioned metal with an acid.
[0100] <Colloidal particles (B) containing a composite oxide of silicon dioxide and tin oxide>
[0101] The colloidal particles (B) of the composite oxide containing silicon dioxide and tin oxide are particles having an average primary particle size of 1 to 4 nm.
[0102] Examples of the colloidal particles (B) include SnO 2 —SiO 2 composite colloidal particles in which SnO 2 particles and SiO 2 particles are composited by chemical bonds at their interfaces.
[0103] In the colloidal particles (B), the mass ratio of silicon dioxide (SiO 2 ) to tin oxide (SnO 2 ) may be, for example, SiO 2 / SnO 2 = 0.1 to 5.0.
[0104] In addition, the colloidal particles (B) may contain other components besides silicon dioxide and tin oxide, and may contain, for example, one or more atoms selected from Al, Zr, Mo, Sb and W. Examples of the forms of these oxides include Al2O3, ZrO2, MoO3, Sb2O5, WO3 and the like.
[0105] As an example of colloidal particles (B) containing other components besides silicon dioxide and tin oxide, there can be cited SnO2-WO3-SiO2 composite colloidal particles in which SnO2 particles, WO3 particles and SiO2 particles are chemically bonded at their interfaces to form a composite, and SnO2-MoO3-SiO2 composite colloidal particles in which SnO2 particles, MoO3 particles and SiO2 particles are chemically bonded at their interfaces to form a composite.
[0106] The composite oxide colloidal particles (B) can be produced by known methods such as ion exchange and oxidation. As an example of the ion exchange method, there is a method in which the acidic salts of the atoms constituting the composite oxide: Sn and Si (and other atoms as required) are treated with a hydrogen-type ion exchange resin. As an example of the oxidation method, there is a method in which the powders of the atoms (Sn and Si, etc.) or their oxides are reacted with hydrogen peroxide.
[0107] <Oxide colloidal particles containing titanium oxide (C)>
[0108] In the titanium oxide colloidal particles (C) containing titanium oxide, which are formed by using the above-mentioned titanium oxide-containing metal oxide colloidal particles (A) as cores and coating the core surfaces with a coating formed by colloidal particles (B) containing the above-mentioned silicon dioxide and oxidized composite oxides (colloidal particles coated with composite oxides - metal oxide colloidal particles containing titanium oxide), the amount (mass ratio) of the composite oxide colloidal particles (B) serving as the coating is preferably in the range of 0.01 to 1.0 relative to the titanium oxide-containing metal oxide colloidal particles (A) serving as the cores.
[0109] In addition, the average primary particle size of the composite oxide colloidal particles (B) is preferably smaller than the average primary particle size of the metal oxide colloidal particles (A) containing titanium oxide. In the oxide colloidal particles (C) containing titanium oxide, it is considered that the composite oxide colloidal particles (B) are coated on the surface of the metal oxide colloidal particles (A) containing titanium oxide by electrostatic action.
[0110] In order to obtain the above-mentioned titanium oxide-containing oxide colloidal particles (C), that is, colloidal particles in which the above-mentioned metal oxide colloidal particles (A) containing titanium oxide are used as cores and the core surfaces are coated with a coating formed by the above-mentioned composite oxide colloidal particles (B), a conventionally known method can be used.
[0111] For example, an aqueous sol containing metal oxide colloidal particles (A) containing titanium oxide as a core and an aqueous sol containing composite oxide colloidal particles (B) serving as a coating are mixed so that the mass ratio of (B) / (A) calculated as the mass of the metal oxide containing titanium oxide and the composite oxide is 0.01 to 1.0, and then the aqueous medium is heated.
[0112] The mixing of the metal oxide colloidal particles (A) containing titanium oxide and the composite oxide colloidal particles (B) can be performed at a temperature of 0 to 100° C., preferably at room temperature to 60° C. Furthermore, the heating after the mixing is performed at, for example, 70 to 300° C.
[0113] 〈Middle film layer〉
[0114] The above-mentioned titanium oxide-containing oxide colloidal particles (C) may have one or more intermediate thin film layers between the above-mentioned titanium oxide-containing metal oxide colloidal particles (A) serving as the core and the coating formed by the colloidal particles (B) containing the composite oxide of silicon dioxide and tin oxide covering the surface thereof, wherein the intermediate thin film layer is formed of any one of a single oxide of at least one atom selected from Si, Al, Sn, Zr, Sb, Nb, Ta and W, a composite oxide of two or more atoms selected from the above group, or a mixture of two or more oxides selected from the single oxide and the composite oxide. The intermediate thin film layer may be one layer or a plurality of layers of two or more.
[0115] By providing at least one intermediate film layer between the colloidal particles (A) serving as the core and the colloidal particles (B) serving as the coating, the refractive index of the oxide colloidal particles (C) containing titanium oxide can be adjusted. That is, the refractive index of the modified oxide colloidal particles containing titanium oxide, which are formed by bonding an organic silicon compound to the surface of the colloidal particles (C), as the (T) component of the present invention described later, can be adjusted. Furthermore, in addition to the improvement of the light resistance and weather resistance of the cured film obtained by using the reactive silicone composition containing the modified oxide colloidal particles containing titanium oxide ((T) component) described later, the various physical properties such as the adhesion between the cured film and the substrate can also be improved. Furthermore, the coloring of the modified oxide colloidal particles containing titanium oxide ((T) component) described later can be suppressed, thereby improving the transparency of the cured film.
[0116] The number and thickness of the intermediate film layer are not particularly limited as long as the amount (mass ratio) of the colloid particles (B) serving as the coating relative to the colloid particles (A) serving as the core is in the range of 0.01 to 1.0.
[0117] In addition, when the above-mentioned intermediate thin film layer is set, it is particularly suitable for the thin film layer to be formed by at least one of silicon dioxide (SiO2), antimony oxide (Sb2O5), aluminum oxide (Al2O3) and zirconium oxide (ZrO2). For example, each component of silicon dioxide, antimony oxide, aluminum oxide or zirconium oxide can be stacked to form a thin film layer. In addition, for example, a thin film layer can be formed by compounding like an antimony oxide-silicon dioxide complex.
[0118] For example, by including silicon dioxide as an oxide constituting the intermediate film layer, the stability of the sol containing the oxide colloidal particles (C) containing titanium oxide (and further the modified oxide colloidal particles containing titanium oxide ((T) component described later)) is improved, and the shelf life of the reactive silicone composition described later is prolonged. Therefore, the hardness of the cured product (cured film, transparent film, etc.) obtained from the reactive silicone composition is improved, and the adhesion to the molded product (cured film, transparent film, etc.) that can be formed on the cured product (cured film, transparent film, etc.) is improved, and the weather resistance, light resistance, adhesion to the substrate, (film) hardness, scratch resistance, flexibility, etc. are improved. For example, if silica and zirconium oxide and / or aluminum oxide are used as the intermediate film layer, it is possible to obtain oxide colloidal particles (C) containing titanium oxide (and further modified oxide colloidal particles ((T) component)) that are capable of forming a cured product (cured film, transparent coating, etc.) having excellent weather resistance, light resistance, adhesion to the substrate, (film) hardness, scratch resistance, flexibility, etc.
[0119] In addition, by using zirconium oxide as an oxide constituting the intermediate film layer, discoloration of the obtained oxide colloidal particles (C) containing titanium oxide (and then the modified oxide colloidal particles ((T) component) containing titanium oxide described later) can be suppressed. Titanium oxide (titanium oxide sol) with a small primary particle size partially undergoes a reduction reaction from TiO2 to TiO by ultraviolet rays, and has the problem of showing a dark blue color as described above. In tin oxide (SnO2), if it becomes a sol with an average primary particle size of less than 100nm, especially less than 30nm, a reduction reaction from SnO2 to SnO also partially occurs by ultraviolet rays, so there is a problem of showing a brown or bluish green color. At this time, by the presence of zirconium oxide in the intermediate film layer of the oxide colloidal particles (C) containing titanium oxide (and then the modified oxide colloidal particles ((T) component) containing titanium oxide), the reduction of titanium oxide and tin oxide constituting the oxide colloidal particles to TiO and SnO can be suppressed, thereby suppressing discoloration.
[0120] In the case of passing through an intermediate film layer, first, an aqueous solution or a colloidal particle dispersion of atoms constituting the intermediate film layer is prepared, into which the metal oxide colloidal particles (A) containing titanium oxide as cores are added, and the intermediate film layer is formed on the surface of the colloidal particles (A). When forming the intermediate film layer, it is preferably heated, preferably at 40° C. or more, or 200° C. or less.
[0121] Then, the coating is formed by adding an aqueous sol of the colloidal particles (B) of the composite oxide to form the coating to the aqueous sol of the colloidal particles (A) forming the intermediate film layer. As mentioned above, the amount of the inorganic oxide colloidal particles (B) added is in the range of 0.01 to 1.0 (mass ratio) relative to the metal oxide colloidal particles (A).
[0122] <Aqueous sol containing titanium oxide colloidal particles (C)>
[0123] The titanium oxide-containing oxide colloidal particles (C) obtained by the above steps are obtained in the form of an aqueous sol of the titanium oxide-containing oxide colloidal particles (C).
[0124] The aqueous sol containing the titanium oxide colloidal particles (C) can be washed to remove impurities as needed. In addition, the total metal oxide concentration in the aqueous sol can be adjusted by ultrafiltration, evaporation concentration, etc., or the pH and temperature of the aqueous sol can be appropriately adjusted. Furthermore, it can be heated to, for example, 40°C to 200°C as needed.
[0125] When the concentration of the aqueous sol is to be further increased, it can be concentrated to a maximum of about 50% by mass by conventional methods, such as evaporation, ultrafiltration, etc. In addition, when the pH of the sol is to be adjusted, an alkali metal, an organic base (amine), a hydroxycarboxylic acid, etc. described below can be added to the sol after concentration.
[0126] In addition, in this specification, the so-called "total metal oxide concentration" in the colloidal particles (C) and the modified colloidal particles formed by bonding an organic silicon compound to the surface of the colloidal particles (C) described later is defined as the concentration including the metal oxides such as TiO2 and SnO2 contained in the colloidal particles (A) and the colloidal particles (B), as well as the concentration of SiO2 as an inorganic oxide contained in the colloidal particles (B).
[0127] In addition, in the aqueous sol of the oxide colloidal particles (C) containing titanium oxide, an organic solvent dispersed sol (organosol) is obtained by replacing the aqueous medium (water) as the dispersion medium of the aqueous sol with an organic solvent. The replacement can be carried out by common methods such as distillation and ultrafiltration. As examples of the organic solvent, lower alcohols such as methanol, ethanol, and isopropanol, cellosolves such as methyl cellosolve and ethyl cellosolve, glycols such as ethylene glycol, ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethyl ether, and tetrahydrofuran, esters such as methyl acetate and ethyl acetate, ketones such as acetone, 2-butanone, and cyclohexanone, halogenated hydrocarbons such as dichloroethane, aromatic hydrocarbons such as toluene and xylene, straight-chain amides such as N,N-dimethylformamide and N,N-dimethylacetamide, cyclic amides such as N-methyl-2-pyrrolidone, etc. can be cited. These organic solvents can be used alone or in combination.
[0128] The sol containing the titanium oxide colloidal particles (C) may contain any other components as long as the purpose of the present invention can be achieved. For example, if the sol contains hydroxycarboxylic acids in a ratio of about 30% by mass or less relative to the total amount of all metal oxides, a colloid having further improved properties such as dispersibility can be obtained. Examples of the hydroxycarboxylic acids used include lactic acid, tartaric acid, citric acid, gluconic acid, malic acid, glycolic acid, and the like.
[0129] In addition, the sol containing the oxide colloidal particles (C) of titanium oxide may contain an alkali component, for example, hydroxides of alkali metals such as Li, Na, K, Rb, Cs, etc.; organic bases such as alkylamines such as ammonia, ethylamine, triethylamine, isopropylamine, n-propylamine, tripentylamine, arylalkylamines such as benzylamine, alicyclic amines such as piperidine, monoethanolamine, alkanolamines such as triethanolamine, etc. They may contain one alone or two or more in a mixture. These alkali components may be contained in a ratio of about 30% by mass or less relative to the total amount of all metal oxides. In addition, it may be used in combination with the above-mentioned hydroxycarboxylic acid.
[0130] <Modified titanium oxide-containing oxide colloidal particles having an organosilicon compound bonded to at least a portion of the surface>
[0131] The component (T) used in the present invention: modified oxide colloidal particles containing titanium oxide, wherein an organosilicon compound is bonded to at least a portion of the surface of the oxide colloidal particles (C) containing titanium oxide. The surface of the colloidal particles is hydrophobized by the surface modification treatment with the organosilicon compound, thereby making the colloidal particles excellently dispersible in water-insoluble organic solvents.
[0132] The particles have a structure in which, for example, an organic silicon compound (e.g., a hydrolyzable reactive group in a compound represented by general formula (1) to (4) described below) is bonded to a hydroxyl group derived from a composite oxide colloidal particle (B) as a coating in an oxide colloidal particle (C) containing titanium oxide.
[0133] As the organosilicon compound to be used, publicly known organosilicon compounds and silane compounds known as silane coupling agents can be used, and the type thereof is appropriately selected depending on the application, the type of solvent, and the like.
[0134] Specific examples of the silane coupling agent include vinyl trichlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methylbistriethoxysilane, 3-glycidoxypropyl triethoxysilane, p-vinylphenyl trimethoxysilane, 3-methacryloxypropyl methyldimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyldiethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane, N-2-(aminoethyl)-3-amino propylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-[methoxy-poly(ethyleneoxy)propyl]trimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, etc.
[0135] In addition, specific examples of the above-mentioned silanes include methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, phenyltrichlorosilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, decyltrimethoxysilane, trifluoropropyltrimethoxysilane, hexamethyldisilazane, etc.
[0136] In addition, for example, as the organic silicon compound, compounds represented by the following general formulas (1) to (4) can be used.
[0137] General formula (1): R 23SiX 2 The monofunctional silane shown
[0138] General formula (2): R 2 2SiX 2 2 shows the difunctional silane
[0139] General formula (3): R 2 SiX 2 3 The trifunctional silane
[0140] General formula (4): SiX 2 The tetrafunctional silane shown in 4
[0141] In the above formulas (1) to (4), R 2 The organic group is an alkyl group having 1 to 8 carbon atoms, a phenyl group, a vinyl group, a methacryloxy group, a mercapto group, an amino group, or an epoxy group.
[0142] X 2 It represents a hydrolyzable reactive group, and preferably includes the groups exemplified as the group X in the compound represented by the above formula [2].
[0143] The organosilicon compound bonded to the surface of the oxide colloidal particles (C) containing titanium oxide may be used alone or in combination of two or more.
[0144] When the surface modification treatment is performed to bond the organosilicon compound to the surface of the titanium oxide-containing oxide colloidal particles (C), the organosilicon compound may be partially hydrolyzed, or the surface modification treatment may be performed directly without hydrolysis.
[0145] After the surface modification treatment, the hydrolyzable reactive groups of the organosilicon compound are preferably reacted with the hydroxyl groups on the surface of the titanium oxide-containing oxide colloidal particles (C), but some hydroxyl groups may remain without being treated.
[0146] In order to combine the organosilicon compound with the surface of the above-mentioned oxide colloidal particles (C) containing titanium oxide, for example, it is sufficient to mix a specified amount of the above-mentioned colloidal particles (C) (for example, a sol of the colloidal particles (C)) in an alcohol solution of the organosilicon compound, add (if necessary) a specified amount of water and a hydrolysis catalyst such as dilute hydrochloric acid as required, and then leave it at room temperature for a specified time, or perform a heat treatment.
[0147] Alternatively, the method may be carried out by adding the hydrolyzate of the organosilicon compound and the colloidal particles (C) to a mixed liquid of water and alcohol and subjecting the mixture to a heat treatment.
[0148] In addition, the amount of the organic silicon compound bound to the surface of the above-mentioned oxide colloidal particles (C) containing titanium oxide (the amount of the organic silicon compound added) is not particularly limited, and for example, it is 0.1 to 40% by mass, for example, 3 to 30% by mass, and preferably 5 to 20% by mass, relative to the total mass of all metal oxides in the colloidal particles (C).
[0149] The modified oxide colloidal particles containing titanium oxide formed by the obtained organic silicon compound bonded to the surface can be obtained in the form of an organic solvent dispersed sol (organosol), and the organic solvent serving as the dispersion medium can be replaced with the desired organic solvent by solvent replacement methods such as the above-mentioned distillation method and ultrafiltration method.
[0150] In the present invention, a sol having a total metal oxide concentration (total metal oxide concentration, including SiO2 for convenience) of, for example, 0.01 to 60% by mass can be used in an organic solvent dispersion sol (organosol) (also referred to as a modified titanium oxide colloidal particle dispersion liquid) of modified oxide colloidal particles containing titanium oxide bonded to the surface by the above-mentioned organic silicon compound. In addition, a sol having a total metal oxide concentration of, for example, 10 to 40% by mass can be cited as a preferred substance. For example, by making a sol having a total metal oxide concentration of 0.01% by mass or more, it becomes easy to form a desired shape (thickness, etc.) when a cured product is obtained from a composition obtained by mixing with other components. In addition, by making a sol having a concentration of less than 60% by mass, it can be expected to be a sol with good stability.
[0151] 《Reactive silicone composition》
[0152] The reactive organosilicon composition of the present invention comprises the above-mentioned component (S): a reactive organosilicon compound, and component (T): modified oxide colloidal particles containing titanium oxide.
[0153] The ratio of the above-mentioned (S) component to the (T) component is not particularly limited. For example, the modified titanium oxide-containing oxide colloidal particles of the (T) component may be contained in an amount of 10 to 500 parts by mass, for example, 25 to 400 parts by mass, relative to 100 parts by mass of the reactive organosilicon compound of the (S) component. In addition, when a reactive diluent described later is contained, the (T) component may be contained in an amount of 10 to 500 parts by mass relative to 100 parts by mass of the total of the (S) component and the reactive diluent.
[0154] <Reactive diluent>
[0155] The reactive organosilicon compound (S) contained in the reactive organosilicon composition of the present invention may have high viscosity and poor workability, so a reactive diluent may be added to adjust the viscosity to an appropriate level. In this case, the reactive diluent is required to have a property that does not significantly reduce heat resistance.
[0156] Examples of such a reactive diluent include compounds having at least one polymerizable group selected from an alkenyl group and a (meth)acryloyl group.
[0157] Examples of the compound having the polymerizable group include one or more compounds selected from the group consisting of compounds represented by the following formula [3] and compounds represented by the following formula [4]. These compounds may be used alone or in combination of two or more.
[0158]
[0159] In formula [3], R 3 represents a hydrogen atom or a methyl group.
[0160] L represents a single bond, a hydrogen atom, an oxygen atom, an m-valent aliphatic hydrocarbon residue having 1 to 20 carbon atoms which may be substituted with a phenyl group, an m-valent aliphatic hydrocarbon residue having 1 to 20 carbon atoms which may optionally contain an ether bond, or a polyol residue having 1 to 20 carbon atoms which may optionally contain an ether bond.
[0161] Ar 3 It represents an n+1-valent aromatic hydrocarbon residue, a monocyclic hydrocarbon residue, a bicyclic hydrocarbon residue, or a tricyclic hydrocarbon residue.
[0162] m represents an integer of 1 to 3 (wherein m represents 1 when L represents a hydrogen atom, and represents 2 when L represents a single bond or an oxygen atom), and n represents 1 or 2 independently of one another.
[0163] Examples of L include methyl, ethyl, n-propyl, isopropyl, n-butyl, n-hexyl, cyclohexyl, benzyl, phenethyl, methoxymethyl, ethoxymethyl, 2-methoxyethyl, methylene, ethylene, 1,3-propylene, 1-methylethylene, propane-2,2-diyl, 1,4-butylene, 1,5-pentylene, 2,2-dimethyl-1,3-propylene, 1,6-hexylene, 3-methyl-1,5-pentylene, cyclohexane-1,4-diyl, diethylene glycol residue (-CH2CH2OCH2CH2-), triethylene glycol residue (-(C H2CH2O)2CH2CH2-), dipropylene glycol residue (-CH(CH3)CH2OCH(CH3)CH2-), 1,3-propylene glycol residue (-CH2CH2CH2-), di(1,3-propylene glycol) residue (-CH2CH2CH2OCH2CH2CH2-), propane-1,1,1-triyl (-C(-)2CH2CH3), propane-1,1,3-triyl (-CH(-)CH2CH2-), butane-1,2,4-triyl (-CH2CH(-)CH2CH2-), etc.
[0164] As Ar3 Examples of Ar include groups obtained by removing n+1 hydrogen atoms from an aromatic hydrocarbon ring such as benzene, naphthalene, anthracene, etc. (phenyl residue, naphthyl residue, anthracene residue). 3 It is preferably substituted or unsubstituted with an alkyl group having 1 to 6 carbon atoms. 3 More preferably it represents a phenyl residue.
[0165] In addition, independently of it, preferably R 3 Represents a hydrogen atom.
[0166] In another independent preferred embodiment, n in formula [3] is 2. Further preferably, Ar 3 represents a phenyl residue and R 3 represents a hydrogen atom. More preferably, Ar 3 represents a phenyl residue, R 3 represents a hydrogen atom and n is 2.
[0167] Furthermore, in all embodiments of the above formula [3], it is most preferred that L represents a hydrogen atom and m is 1.
[0168]
[0169] In formula [4], R 4 represents a hydrogen atom or a methyl group.
[0170] R 5 It represents a p-valent aliphatic hydrocarbon residue having 1 to 20 carbon atoms which may be optionally substituted with a phenyl group, or a p-valent aliphatic hydrocarbon residue having 1 to 20 carbon atoms which may optionally contain an ether bond.
[0171] p represents an integer of 1 to 6.
[0172] As R in formula [4] 5Examples of the alkyl radical include methyl, ethyl, n-propyl, isopropyl, n-butyl, n-hexyl, cyclohexyl, benzyl, phenethyl, methoxymethyl, ethoxymethyl, 2-methoxyethyl, methylene, ethylene, 1,3-propylene, 1-methylethylene, propane-2,2-diyl, 1,4-butylene, 1,5-pentylene, 2,2-dimethyl-1,3-propylene, 1,6-hexylene, 3-methyl-1,5-pentylene, cyclohexane-1,4-diyl, diethylene glycol residue (-CH2CH2OCH2CH2-), triethylene glycol residue (-(CH 2CH2O)2CH2CH2-), dipropylene glycol residue (-CH(CH3)CH2OCH(CH3)CH2-), 1,3-propylene glycol residue (-CH2CH2CH2-), di(1,3-propylene glycol) residue (-CH2CH2CH2OCH2CH2CH2-), propane-1,1,1-triyl (-C(-)2CH2CH3), propane-1,1,3-triyl (-CH(-)CH2CH2-), butane-1,2,4-triyl (-CH2CH(-)CH2CH2-), etc.
[0173] In the above formula [4], R is more preferably 5 represents a polyol residue having 2 to 10 carbon atoms which may optionally contain an ether bond, and p represents an integer of 2 to 6.
[0174] In order to produce a cured product having desired transparency at near-infrared wavelengths of 850 nm, 1.31 μm, and 1.55 μm, it should be noted that one or more compounds represented by formula [3] are preferably used as the reactive diluent.
[0175] Specific examples of the compounds represented by formulas [3] and [4] are described below, but the compounds are not limited thereto.
[0176] Specific examples of the compound represented by formula [3] include divinylbenzene, styrene, diisopropenylbenzene, 4,4′-divinylbiphenyl, 2-(4-vinylphenoxy)styrene, 4-phenethylstyrene, and 1,1,1-tris(4-vinylphenoxy)propane.
[0177] Specific examples of the compound represented by formula [4] include benzyl (meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, The invention also includes the following: meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethylene glycol diglycidyl ether (meth)acrylate adduct, propylene glycol diglycidyl ether (meth)acrylate adduct, etc. In addition, in the present specification, the descriptions such as (meth)acrylate and (meth)acrylic acid respectively represent both methacrylate and acrylate, and methacrylic acid and acrylic acid.
[0178] When a reactive diluent is used in the reactive silicone composition of the present invention, the compound having at least one polymerizable group selected from alkenyl groups and (meth)acryloyl groups as the reactive diluent is used in a ratio of 1 to 100 parts by mass, preferably 5 to 70 parts by mass, based on 100 parts by mass of the reactive silicone compound.
[0179] For example, when the compound represented by formula [3] is used as the reactive diluent, it can be used in a ratio of 1 to 100 parts by mass, preferably 5 to 70 parts by mass, for example 5 to 20 parts by mass, based on 100 parts by mass of the reactive organosilicon compound.
[0180] When the compound represented by the formula [4] is used as the reactive diluent, it can be used in a ratio of 1 to 100 parts by mass, preferably 5 to 50 parts by mass, based on 100 parts by mass of the reactive organosilicon compound.
[0181] In addition, ratios other than the above ratios are also possible in the same manner.
[0182] The reactive silicone composition of the present invention may contain a solvent for the purpose of imparting fluidity, adjusting the solid content concentration, adjusting the surface tension, viscosity, evaporation rate, etc.
[0183] The solvent used is not limited as long as it can dissolve or disperse the components contained in the reactive silicone composition, and is, for example, water or an organic solvent.
[0184] Examples of the organic solvent include alcohols such as methanol, ethanol, isopropanol, and butanol, cellosolves such as methyl cellosolve and ethyl cellosolve, glycols such as ethylene glycol, esters such as methyl acetate, ethyl acetate, and butyl acetate, ethers such as diethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and tetrahydrofuran, ketones such as acetone, 2-butanone, and cyclohexanone, halogenated hydrocarbons such as dichloroethane, aromatic hydrocarbons such as toluene and xylene, and N,N-dimethylformamide, N-methyl-2-pyrrolidone, etc. Among them, cyclohexanone and 2-butanone can be mentioned as suitable solvents.
[0185] In addition, the concentration of the total solid content in the reactive silicone composition of the present invention can be appropriately selected according to the purpose of controlling the thickness and coating properties, and can be, for example, 1 to 99 mass%, 10 to 80 mass%, 20 to 40 mass%, or 30 to 70 mass%. In addition, in this specification, the so-called "total solid content" refers to all components after removing the solvent from the reactive silicone composition, and even if it is a liquid component, it is also treated as a "solid component" for convenience.
[0186] In addition, the reactive silicone composition may have a viscosity of, for example, 0.1 to 200 mPa·s or 0.5 to 50 mPa·s from the viewpoint of workability in a coating device such as a coater.
[0187] Furthermore, the reactive silicone composition of the present invention may contain various surfactants, leveling agents, etc., for the purpose of improving wettability to the substrate and smoothness of the cured film when the composition forms a cured product (cured film) on the substrate as described below. Furthermore, ultraviolet absorbers, antioxidants, light stabilizers, antistatic agents, etc. may be added as long as they do not affect the physical properties of the cured film. Furthermore, disperse dyes, oil-soluble dyes, fluorescent dyes, pigments, photochromic compounds, thixotropic agents, etc. may be added.
[0188] In addition, various fine-particle metal oxides may be included in the reactive silicone composition of the present invention in order to match the refractive index of the substrate (base material such as lens). Examples of the fine-particle metal oxides include fine particles of aluminum oxide, titanium oxide, antimony pentoxide, zirconium oxide, silicon dioxide, cerium oxide, etc. having an average primary particle size of 2 to 60 nm.
[0189] 〔Cured product〕
[0190] The reactive silicone composition of the present invention can be cured by reacting the polymerizable double bonds contained in the reactive silicone compound by irradiation with light (active energy rays) or heating in the absence of a polymerization initiator or in the presence of a photoradical polymerization initiator or a thermal radical polymerization initiator. In addition, the reactive silicone composition containing a polymerization initiator is also the subject of the present invention.
[0191] The obtained cured product (molded product) is useful as an optical device material, for example, as an optical interconnect material, specifically, can be used as a core member in an optical signal transmission cable.
[0192] Furthermore, due to the property that the cured product is useful as an optical device material, the reactive silicone composition itself can be used as an optical adhesive used for connecting optical waveguides or connecting an optical waveguide and a light receiving element in an optical signal transmission device.
[0193] Examples of the photoradical polymerization initiator include acetophenones, benzophenones, Michler's benzoylbenzoate, amidoxime esters, tetramethylthiuram monosulfide, and thioxanthones.
[0194] When a photoradical polymerization initiator is used, a photocleavage-type photoradical polymerization initiator can be cited as a preferred example. As for the photocleavage-type photoradical polymerization initiator, the substances described in Latest UV Curing Technology (Latest UV Curing Technology) (page 159, publisher: Kazuhiro Takahashi, publisher: Technical Information Association Co., Ltd., published in 1991) can be cited.
[0195] Examples of commercially available photoradical polymerization initiators include OMNIRAD (registered trademark, former name: Ilgacur) 184, 369, 651, 500, 819, 907, 784, 2959, CGI1700, CGI1750, CGI1850, CG24-61, OMNIRAD (registered trademark), manufactured by IGM Corporation. , old name: ダロキュア) 1116, 1173, OMNIRAD (registered trademark, old name: ルシリン) TPO, UCB Co., Ltd. Trade names: ユベクリルP36, フラテツTrade names made by リ·ランベルティ Co., Ltd.: エザキュアーKIP150, KIP65LT, KIP100F, KT37, KT55, KTO46, KIP75 / B, etc.
[0196] Examples of the thermal radical polymerization initiator include the following.
[0197] 1) Peroxides:
[0198] For example, tert-butyl (3,5,5-trimethylhexanoyl) peroxide, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl peroxyoctanoate, tert-butyl peroxyneodecanoate, tert-butyl peroxyisobutyrate, lauroyl peroxide, tert-amyl peroxypivalate, tert-butyl peroxypivalate, dicumyl peroxide, benzoyl peroxide, potassium persulfate, ammonium persulfate, etc.;
[0199] 2) Azo compounds:
[0200] For example, 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-butyronitrile), 4,4'-azobis(4-pentanoic acid), 1,1'-azobis(cyclohexanecarbonitrile), 2-(tert-butylazo)-2-cyanopropane, 2,2'-azobis[2-methyl-N-(1,1)-bis(hydroxymethyl)-2-hydroxyethyl]propionamide, 2,2'-azobis(2-methyl-N-hydroxyethyl)propionamide, 2,2'-azobis(N,N-dimethylene isobutylamidine) dichloride, 2,2'-azobis(2-amidinopropane) dichloride, 2,2'-azobis(N,N-dimethyleneisobutylamide), 2,2'-azobis(2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide), 2,2'-azobis(2-methyl-N-[1,1-bis(hydroxymethyl)ethyl]propionamide), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide), 2,2'-azobis(isobutylamide) dihydrate, etc.;
[0201] 3) A redox system comprising the following combinations:
[0202] - A mixture of hydrogen peroxide or alkyl peroxides, peresters, percarbonates, etc. with any of ferric salts or titanous salts, zinc formaldehyde sulfoxylate or sodium formaldehyde sulfoxylate, and reducing sugars;
[0203] - a combination of an alkali metal or ammonium salt of persulfate, perborate or perchlorate with an alkali metal bisulfite such as sodium pyrosulfite and a reducing sugar;
[0204] - Combinations of alkali metal persulfate, arylphosphonic acid such as phenylphosphonic acid, other similar acids, and reducing sugars.
[0205] When a polymerization initiator is used, the amount of the photo-radical polymerization initiator or the thermal-radical polymerization initiator used is based on 100 parts by mass of the reactive organosilicon compound of the component (S), and when a reactive diluent is included, it is, for example, in the range of 0.1 to 15 parts by mass, or in the range of 0.5 to 10 parts by mass based on 100 parts by mass of the total of the component (S) and the reactive diluent. The polymerization initiator may be used alone or in combination of multiple initiators.
[0206] Examples of active energy rays used for the reaction (curing) of the reactive silicone composition include infrared rays, ultraviolet rays, and electron rays.
[0207] The heating temperature is, for example, 70 to 200°C, or 90 to 150°C.
[0208] Before the light irradiation and heating, preheating may be performed in order to remove the solvent contained in the reactive silicone composition.
[0209] Furthermore, the reactive silicone composition of the present invention can be applied to the surface of a substrate and a cured film can be obtained by light irradiation or heating, that is, it can also be used as a coating composition. In addition, a film-forming agent formed by the above-mentioned reactive silicone composition is also the subject of the present invention. Furthermore, by using a transparent substrate (optical substrate) suitable for optical use, an optical component having a cured film (transparent film) can be obtained.
[0210] As the substrate used, various substrates formed of glass, plastic, etc. are used, for example, diaphragms, silicon wafer substrates, silicon / silicon dioxide coated substrates, silicon nitride substrates, glass substrates, ITO substrates, polyimide substrates, and low dielectric constant material (low-k material) coated substrates can be cited.
[0211] Specific examples of the substrate to which it is applied include eyeglass lenses, various optical lenses such as cameras, various display element filters, looking glasses, window glass, paint films for automobiles, lamp covers for automobiles, etc. The cured film formed on the surface of the substrate can be used for applications such as hard coating films and primer films for plastic lenses.
[0212] As a method for applying the reactive silicone composition on the surface of the substrate, a commonly used method such as dipping, spinning, spraying, etc. can be applied. For example, from the viewpoint of area coverage, dipping or spinning can be selected.
[0213] In addition, curing after coating can be performed by hot air drying or active energy ray irradiation. As the curing conditions of hot air drying, it is preferably performed in hot air at 70 to 200° C., and particularly preferably at 90 to 150° C. In addition, as active energy rays, infrared rays, ultraviolet rays, electron rays, etc. can be cited, and in particular, far infrared rays can suppress the damage caused by heat to a low level.
[0214] In addition, before applying the reactive silicone composition on the substrate surface, the substrate surface may be subjected to chemical treatment using an acid, alkali or various organic solvents or detergents, or physical treatment using plasma, ultraviolet rays, etc., to improve the adhesion between the substrate and the cured film. The adhesion between the substrate and the cured film may be further improved by subjecting the substrate surface to a primer treatment using various resins.
[0215] Furthermore, the cured film formed from the reactive silicone composition of the present invention can be used as a high refractive index film for a reflective film, and can also be used as a multifunctional film by adding functional components such as antifogging, photochromic, and antifouling.
[0216] The optical member having a cured film formed from the reactive silicone composition of the present invention can be used as not only eyeglass lenses but also camera lenses, automobile window glass, and optical filters attached to liquid crystal displays, plasma displays, and the like.
[0217] In addition, the optical component has a cured film formed of the reactive silicone composition of the present invention on the surface of the optical substrate, and an anti-reflection film composed of a vapor-deposited film of an inorganic oxide can be formed on the cured film. The anti-reflection film is not particularly limited, and a single-layer or multi-layer vapor-deposited film of a conventionally known inorganic oxide can be used. Examples of anti-reflection films include anti-reflection films disclosed in Japanese Patent Application Publication No. 2-262104 and Japanese Patent Application Publication No. 56-116003.
[0218] Example
[0219] Hereinafter, the present invention will be described in further detail based on Production Examples, Examples, and Comparative Examples, but the present invention is not limited to these Examples at all.
[0220] The physical properties of the dispersion were determined by the following measurement methods.
[0221] ·Viscosity: measured by BL type viscometer. (20°C)
[0222] Solid content concentration: Calculated from the residual solid matter after calcination at 600°C.
[0223] Average particle size obtained by dynamic light scattering (dynamic light scattering particle size):
[0224] The sol was diluted with a dispersion solvent, and the parameters of the solvent were used to measure the dynamic light scattering method using a laser particle size analyzer (Zetasizer) manufactured by Malvern Instruments Ltd.
[0225] Average primary particle size obtained by transmission electron microscopy: The sol was dropped onto a copper grid and dried. The sol was observed using a transmission electron microscope (JEM-1020 manufactured by JEOL Ltd.) at an accelerating voltage of 100 kV. 100 particles were measured and the average value was determined as the average primary particle size.
[0226] In addition, the reactive silicone compositions prepared and used in Examples 1 to 13, the comparative example compositions prepared and used in Comparative Examples 1 and 2, and the cured films obtained from these compositions were evaluated by measuring various physical properties in the following procedures.
[0227] (1) Storage stability evaluation
[0228] Each composition was stored in a dryer set at 5° C. for 1 day, and the appearance before and after storage was visually checked, and the presence or absence of changes was evaluated based on the following criteria. The obtained evaluation results are shown in Table 1 [Table 1-1, Table 1-2].
[0229] A: No precipitate is generated and the material has fluidity.
[0230] N: Precipitates were generated and gelled.
[0231] (2) Transmittance in infrared region
[0232] The average transmittance of each cured film formed on the glass substrate was measured at a measurement wavelength of 800 to 1600 nm using an ultraviolet-visible-near-infrared spectrophotometer (UV-3600 manufactured by Shimadzu Corporation).
[0233] (3) Haze value
[0234] The haze value of each cured film formed on the glass substrate was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries, Ltd.).
[0235] (4) Film thickness and refractive index
[0236] The reflectance of each cured film formed on the glass substrate was measured using a lens reflectance measuring machine (USPM-RU, manufactured by Orion Pass Co., Ltd.) and the film thickness was calculated from the measured reflectance using optical simulation.
[0237] (5) Light resistance test
[0238] The transmittance of each cured film formed on the glass substrate was measured using a spectrophotometer (UV-3600 manufactured by Shimadzu Corporation), and the YI value was calculated based on JIS 7373.
[0239] Then, a QUV accelerated weathering tester (UVA lamp irradiation intensity 890mW / m 2 ), and the cured film was obtained by exposure for 96 hours, and the YI value of the obtained cured film was calculated.
[0240] From the obtained YI value, ΔYI of the cured film before and after ultraviolet irradiation was calculated. The judgment criteria are as follows.
[0241] A: ΔYI is less than 2.0
[0242] N: ΔYI is 2.0 or more
[0243] [Production Example 1]
[0244] <Preparation of reactive organosilicon compounds>
[0245] A colorless and transparent reactive organosilicon compound was synthesized by the method described in International Publication No. 2012 / 097836. That is, diphenylsilanediol and styryltrimethoxysilane were subjected to dealcoholization condensation in a toluene solvent with barium hydroxide monohydrate as a catalyst under heating at 50°C, and then the mixture was cooled and filtered, and toluene and methanol as a by-product were removed under vacuum using a rotary evaporator under heating at 50°C, thereby synthesizing the target colorless and transparent reactive organosilicon compound.
[0246] A mixed solution containing a reactive organosilicon compound and a reactive diluent is prepared by the method described in International Publication No. 2012 / 097836. That is, divinylbenzene purified by vacuum distillation is added as a reactive diluent to the reactive organosilicon compound obtained above at a predetermined ratio (7 parts by mass relative to 100 parts by mass of the reactive organosilicon compound), and the mixture is stirred and mixed under heating at 40°C to obtain a uniform liquid, and a light yellow transparent mixed solution is obtained after cooling to room temperature. OMNIRAD (registered trademark, old name Lusilin) TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide) manufactured by IGM is added as a photopolymerization initiator at a predetermined ratio (3 parts by mass relative to 100 parts by mass of the total of the reactive organosilicon compound and the reactive diluent), and the mixed solution containing the target reactive organosilicon compound is prepared while being dissolved by stirring.
[0247] [Production Example 2]
[0248] <Synthesis of modified titanium oxide colloidal particle dispersion 1>
[0249] 126.2 g of pure water was added to a 1-liter container, and 17.8 g of metastannic acid (containing 15 g in terms of SnO2), 284 g of titanium tetraisopropoxide (containing 80 g in terms of TiO2), 84 g of oxalic acid dihydrate (70 g in terms of oxalic acid), and 438 g of a 35% by mass tetraethylammonium hydroxide aqueous solution were added under stirring. The molar ratio of oxalic acid / titanium atom in the obtained mixed solution was 0.78, and the molar ratio of tetraethylammonium hydroxide / titanium atom was 1.04. 950 g of the mixed solution was maintained at 80°C for 2 hours, and the pressure was further reduced to 580 torr and maintained for 2 hours to prepare a titanium mixed solution. The pH of the modulated titanium mixed solution was 4.7, the conductivity was 27.2 mS / cm, and the TiO2 concentration was 8.4% by mass.
[0250] 950 g of the titanium mixed solution and 950 g of pure water were placed in a 3-liter glass-lined autoclave container and hydrothermally treated at 140°C for 5 hours. After cooling to room temperature, the hydrothermally treated solution taken out was a light milky white aqueous dispersion of titanium oxide colloidal particles. The pH of the obtained dispersion was 3.9, the conductivity was 19.7 mS / cm, the TiO2 concentration was 4.2% by mass, the tetraethylammonium hydroxide was 4.0% by mass, the oxalic acid was 1.8% by mass, the particle size by dynamic light scattering method was 16 nm, and elliptical particles with an average primary particle size of 5 to 15 nm were observed in transmission electron microscope observation. X-ray diffraction analysis of the powder obtained by drying the dispersion at 110°C confirmed that it was rutile crystals. The obtained titanium oxide colloidal particles were set as metal oxide colloidal particles (A) containing titanium oxide (the titanium oxide concentration in the colloidal particles was 84% by mass) (hereinafter also referred to as core particles (A) containing titanium oxide).
[0251] Next, 27.9 g of sodium silicate aqueous solution (JIS No. 3 sodium silicate, containing 34% by mass as SiO2, manufactured by Fuji Chemical Co., Ltd.) was diluted with 27.9 g of pure water, and 8.6 g of sodium stannate trihydrate (containing 55% by mass as SnO2, manufactured by Showa Chemical Co., Ltd.) was added and dissolved under stirring to obtain a silicate-sodium stannate aqueous solution. 64.4 g of the obtained silicate-sodium stannate aqueous solution was diluted with 411 g of pure water and passed through a column filled with a hydrogen-type cation exchange resin (Anvaliate (registered trademark) IR-120B), thereby obtaining an aqueous dispersion of silica-stannic acid composite oxide colloidal particles (pH 2.7, containing 0.83% by mass as SnO2, containing 1.67% by mass as SiO2, SiO2 / SnO2 mass ratio 2.0) 570 g.
[0252] Next, 2.9 g of diisopropylamine was added to the obtained aqueous dispersion of silica-stannic acid composite oxide colloid particles. The obtained dispersion was an alkaline aqueous dispersion of silica-stannic acid composite oxide colloid particles, and was a colloid particle having a pH of 8.2 and an average primary particle size of 1 to 4 nm. The obtained alkaline silica-stannic acid composite oxide colloid particles (B) were used as colloid particles of the coating described below.
[0253] Next, 570 g of silica-stannic acid composite oxide (B) as a coating was added to 1900 g of the aqueous dispersion of the core particles (A) containing titanium oxide under stirring, and the mixture was kept at a temperature of 95° C. for 3 hours to obtain an aqueous dispersion of oxide colloidal particles (C) containing titanium oxide. Then, the aqueous dispersion of the modified titanium oxide colloidal particles obtained was passed through a column filled with a hydrogen-type cation exchange resin (Anvalite IR-120B) to obtain an acidic aqueous dispersion of oxide colloidal particles containing titanium oxide 2730 g. The pH of the obtained dispersion was 2.7, and the total metal oxide concentration was 4.0% by mass. 5.1 g of tripentylamine was added to the obtained dispersion. Next, the dispersion to which tripentylamine was added was put into an evaporator with an eggplant-shaped flask for concentration, and water was distilled off at 600 torr while methanol was added, thereby obtaining 533 g of a methanol dispersion of oxide colloidal particles (C) containing titanium oxide. The pH of the obtained methanol dispersion was 6.0 (diluted with water of the same mass as the dispersion), the total metal oxide concentration was 20.5% by mass, and the water content was 3.1%. In addition, the average primary particle size obtained by transmission electron microscopy was 8 to 18 nm, and the average particle size (dynamic light scattering method particle size) obtained by dynamic light scattering (DLS) was 15 nm.
[0254] To 400 g of the obtained methanol dispersion of oxide colloidal particles containing titanium oxide (C), 6.9 g of 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., 3-methacryloxypropyltrimethoxysilane) was added, and the mixture was refluxed at 70°C for 5 hours to allow 3-methacryloxypropyl groups to bind to the surface, thereby obtaining a methanol dispersion of modified oxide colloidal particles containing titanium oxide.
[0255] Next, methanol was distilled off while adding cyclohexanone at 150 Torr using an evaporator to replace methanol with cyclohexanone, and 210 g of a cyclohexanone (containing 10% by mass of methanol) dispersion of modified oxide colloid particles containing titanium oxide with 3-methacryloxypropyl groups bonded to the surface (hereinafter referred to as modified titanium oxide colloid particle dispersion 1) was obtained. The pH of the obtained cyclohexanone (containing 10% by mass of methanol) dispersion was 5.9 (diluted with water and methanol of the same mass as the dispersion), and the total metal oxide concentration was 40.0% by mass.
[0256] [Production Example 3]
[0257] <Synthesis of modified titanium oxide colloidal particle dispersion 2>
[0258] To 400 g of a methanol dispersion of oxide colloidal particles (C) containing titanium oxide produced by the same method as in Production Example 2, 6.9 g of 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated under reflux at 70°C for 5 hours to obtain a methanol dispersion of modified oxide colloidal particles containing titanium oxide in which 3-methacryloxypropyl groups were bonded to the surface.
[0259] Next, methanol was distilled off while adding cyclohexanone at 150 Torr using an evaporator to replace methanol with cyclohexanone, and 210 g of a cyclohexanone (containing 20% by mass of methanol) dispersion of modified oxide colloid particles containing titanium oxide with 3-methacryloxypropyl groups bonded to the surface (hereinafter referred to as modified titanium oxide colloid particle dispersion 2) was obtained. The pH of the obtained cyclohexanone (containing 20% by mass of methanol) dispersion was 5.9 (diluted with water and methanol of the same mass as the dispersion), and the total metal oxide concentration was 40.0% by mass.
[0260] [Production Example 4]
[0261] <Synthesis of modified titanium oxide colloidal particle dispersion 3>
[0262] To 400 g of a methanol dispersion of oxide colloidal particles (C) containing titanium oxide produced by the same method as in Production Example 2, 6.9 g of 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated under reflux at 70°C for 5 hours to obtain a methanol dispersion of modified oxide colloidal particles containing titanium oxide in which 3-methacryloxypropyl groups were bonded to the surface.
[0263] Next, 2-butanone was added and methanol was distilled off at 150 Torr using an evaporator to replace methanol with 2-butanone, and 280 g of 2-butanone dispersion of oxide colloidal particles containing modified titanium oxide with 3-methacryloxypropyl groups bonded to the surface (hereinafter referred to as modified titanium oxide colloidal particle dispersion 3) was obtained. The pH of the obtained 2-butanone dispersion was 6.1 (diluted with water and methanol of the same mass as the dispersion), and the total metal oxide concentration was 30.0 mass %.
[0264] [Production Example 5]
[0265] <Synthesis of modified titanium oxide colloidal particle dispersion 4>
[0266] To 400 g of a methanol dispersion of oxide colloidal particles (C) containing titanium oxide produced by the same method as in Production Example 2, 5.5 g of phenyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was refluxed at 70°C for 5 hours to obtain a methanol dispersion of modified oxide colloidal particles containing titanium oxide in which phenyl groups were bonded to the surface.
[0267] Next, 2-butanone was added and methanol was distilled off at 150 Torr using an evaporator to replace methanol with 2-butanone, and 280 g of 2-butanone dispersion of modified oxide colloidal particles containing titanium oxide with phenyl groups bound to the surface (hereinafter referred to as modified titanium oxide colloidal particle dispersion 4) was obtained. The pH of the obtained 2-butanone dispersion was 5.5 (diluted with water and methanol of the same mass as the dispersion), and the total metal oxide concentration was 30.0 mass %.
[0268] [Production Example 6]
[0269] <Synthesis of modified titanium oxide colloidal particle dispersion 5>
[0270] To 400 g of a methanol dispersion of oxide colloidal particles (C) containing titanium oxide produced by the same method as in Production Example 2, 5.8 g of hexyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated under reflux at 70°C for 5 hours to obtain a methanol dispersion of modified oxide colloidal particles containing titanium oxide in which hexyl groups were bonded to the surface.
[0271] Next, 2-butanone was added to the mixture at 150 torr using an evaporator while methanol was distilled off to replace methanol with 2-butanone, and 280 g of a 2-butanone dispersion of oxide colloidal particles containing modified titanium oxide with hexyl groups bonded to the surface (hereinafter referred to as modified titanium oxide colloidal particle dispersion 5) was obtained. The pH of the obtained 2-butanone dispersion was 5.8 (diluted with water and methanol of the same mass as the dispersion), and the total metal oxide concentration was 30.0 mass %.
[0272] [Production Example 7]
[0273] <Synthesis of modified titanium oxide colloidal particle dispersion 6>
[0274] To 400 g of a methanol dispersion of oxide colloidal particles (C) containing titanium oxide produced by the same method as in Production Example 2, 16.8 g of polyether-modified silane (3-[methoxy(polyethyleneoxy)n-propyl]trimethoxysilane (n=5-15)) (produced by Shin-Etsu Chemical Co., Ltd.) was added, and the mixture was heated under reflux at 70°C for 5 hours to obtain a methanol dispersion of modified oxide colloidal particles containing titanium oxide in which polyether groups were bonded to the surface.
[0275] Next, methanol was distilled off while adding 2-butanone at 150 Torr using an evaporator to replace methanol with 2-butanone, and 280 g of 2-butanone dispersion of modified oxide colloidal particles containing titanium oxide with polyether groups bonded to the surface (hereinafter referred to as modified titanium oxide colloidal particle dispersion 6) was obtained. The pH of the obtained 2-butanone dispersion was 6.4 (diluted with water and methanol of the same mass as the dispersion), and the total metal oxide concentration was 30.0 mass %.
[0276] [Production Example 8]
[0277] <Synthesis of Titanium Oxide Colloidal Particle Dispersion Liquid 7>
[0278] 2600 g of the dispersion of the core particles (A) containing titanium oxide produced by the same method as in Production Example 2 was placed in an evaporator with an eggplant-shaped flask for concentration, and water was distilled off at 600 Torr while adding methanol, thereby obtaining 533 g of a methanol dispersion of the core particles (A) containing titanium oxide. The obtained methanol dispersion had a pH of 4.1, a total metal oxide concentration of 20.5% by mass, and a water content of 3.0%.
[0279] 6.9 g of 3-methacryloxypropyltrimethoxysilane was added to 400 g of the obtained methanol dispersion of the titanium oxide-containing core particles (A), and the mixture was heated under reflux at 70° C. for 5 hours to obtain a methanol dispersion of modified titanium oxide-containing core particles having 3-methacryloxypropyl groups bonded to the surface.
[0280] Next, 2-butanone was added and methanol was distilled off at 150 Torr using an evaporator to replace methanol with 2-butanone, and 280 g of a 2-butanone dispersion of core particles containing modified titanium oxide with 3-methacryloxypropyl groups bonded to the surface (hereinafter referred to as titanium oxide colloidal particle dispersion 7) was obtained. The pH of the obtained 2-butanone dispersion was 4.2 (diluted with water and methanol of the same mass as the dispersion), and the total metal oxide concentration was 30.0 mass %.
[0281] [Example 1]
[0282] 2 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 3 g of cyclohexanone, and 5 g of the modified titanium oxide colloidal particle dispersion 1 prepared in Preparation Example 2 was added thereto and mixed, thereby obtaining a light yellow transparent reactive organosilicon composition 1. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 100 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 1. The evaluation results are shown in Table 1 [Table 1-1, Table 1-2].
[0283] The reactive silicone composition 1 was coated on a glass substrate using a spin coater at a rotation speed of 2000 rpm, and heated at 100° C. for 10 minutes using a hot plate to remove the solvent. 2 The irradiation was performed for 3 minutes to obtain a cured film. The obtained cured film was subjected to the tests (2) to (5) described above. The evaluation results are shown in Table 1 [Table 1-1].
[0284] [Example 2]
[0285] When the reactive organosilicon composition 1 described in Example 1 (the amount of the modified titanium-containing oxide colloidal particles to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was applied to the glass substrate, the rotation speed of the spin coater was changed to 1000 rpm. The solvent removal and ultraviolet irradiation were performed in the same manner as in Example 1 to prepare a cured film and evaluate the same. The evaluation results are shown in Table 1 [Table 1-1].
[0286] [Example 3]
[0287] When the reactive organosilicon composition 1 described in Example 1 (the amount of the modified titanium-containing oxide colloidal particles to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was applied to the glass substrate, the rotation speed of the spin coater was changed to 500 rpm. The solvent removal and ultraviolet irradiation were performed in the same manner as in Example 1 to prepare a cured film and evaluate the same. The evaluation results are shown in Table 1 [Table 1-1].
[0288] [Example 4]
[0289] 3.2 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 4.8 g of cyclohexanone, and 2 g of the modified titanium oxide colloidal particle dispersion 1 prepared in Preparation Example 2 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 2. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 25 phr. The obtained reactive organosilicon composition 2 was subjected to the test shown in (1) above. The evaluation results are shown in Table 1 [Table 1-1].
[0290] The reactive silicone composition 2 was applied to the glass substrate at a spin coater speed of 500 rpm, and the solvent removal and ultraviolet irradiation were performed in the same manner as in Example 1 to prepare a cured film and evaluate the results. The evaluation results are shown in Table 1 [Table 1-1].
[0291] [Example 5]
[0292] 0.8 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 1.2 g of cyclohexanone, and 8 g of the modified titanium oxide colloidal particle dispersion 1 prepared in Preparation Example 2 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 3. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 400 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 3. The evaluation results are shown in Table 1 [Table 1-1].
[0293] The reactive silicone composition 3 was applied to the glass substrate at a spin coater speed of 500 rpm, and the solvent removal and ultraviolet irradiation were performed in the same manner as in Example 1 to prepare a cured film and evaluate the results. The evaluation results are shown in Table 1 [Table 1-1].
[0294] [Example 6]
[0295] 2 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 2.4 g of cyclohexanone and 0.6 g of methanol, and 5 g of the modified titanium oxide colloidal particle dispersion 2 prepared in Preparation Example 3 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 4. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 100 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 4. The evaluation results are shown in Table 1 [Table 1-1].
[0296] The reactive silicone composition 4 was applied to a glass substrate using a spin coater at a rotation speed of 1000 rpm, heated on a hot plate at 100° C. for 10 minutes to remove the solvent, and further heated at 120° C. for 2 hours to prepare a cured film, which was evaluated. The obtained evaluation results are shown in Table 1 [Table 1-1].
[0297] [Example 7]
[0298] 3.2 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 3.84 g of cyclohexanone and 0.96 g of methanol, and 2 g of the modified titanium oxide colloidal particle dispersion 2 prepared in Preparation Example 3 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 5. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 25 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 5. The evaluation results are shown in Table 1.
[0299] The reactive silicone composition 5 was applied on a glass substrate, the solvent was removed, and the film was heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-1].
[0300] [Example 8]
[0301] 0.8 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 0.96 g of cyclohexanone and 0.24 g of methanol, and 8 g of the modified titanium oxide colloidal particle dispersion 2 prepared in Preparation Example 3 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 6. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 400 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 6. The evaluation results are shown in Table 1 [Table 1-1].
[0302] The reactive silicone composition 6 was applied on a glass substrate, the solvent was removed, and the film was heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-1].
[0303] [Example 9]
[0304] 1.5 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 3.5 g of 2-butanone, and 5 g of the modified titanium oxide colloidal particle dispersion 3 prepared in Preparation Example 4 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 7. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 100 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 7. The evaluation results are shown in Table 1 [Table 1-2].
[0305] The reactive silicone composition 7 was applied on a glass substrate, the solvent was removed, and the film was heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-2].
[0306] [Example 10]
[0307] 0.6 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 1.4 g of 2-butanone, and 8 g of the modified titanium oxide colloidal particle dispersion 3 prepared in Preparation Example 4 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 8. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 400 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 8. The evaluation results are shown in Table 1 [Table 1-2].
[0308] The reactive silicone composition 8 was applied on a glass substrate, desolvated, and heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-2].
[0309] [Example 11]
[0310] 2.4 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 5.6 g of 2-butanone, and 2 g of the modified titanium oxide colloidal particle dispersion 4 prepared in Preparation Example 5 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 9. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 25 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 9. The evaluation results are shown in Table 1 [Table 1-2].
[0311] The reactive silicone composition 9 was applied on a glass substrate, the solvent was removed, and the film was heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-2].
[0312] [Example 12]
[0313] 2.4 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 5.6 g of 2-butanone, and 2 g of the modified titanium oxide colloidal particle dispersion 5 prepared in Preparation Example 6 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 10. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 25 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 10. The evaluation results are shown in Table 1 [Table 1-2].
[0314] The reactive silicone composition 10 was applied on a glass substrate, the solvent was removed, and the film was heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-2].
[0315] [Example 13]
[0316] 2.4 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 5.6 g of 2-butanone, and 2 g of the modified titanium oxide colloidal particle dispersion 6 prepared in Preparation Example 7 was added thereto and mixed to obtain a light yellow transparent reactive organosilicon composition 11. The amount of the modified titanium oxide colloidal particles (in terms of all metal oxides) blended relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 25 phr. The test shown in (1) above was performed on the obtained reactive organosilicon composition 11. The evaluation results are shown in Table 1 [Table 1-2].
[0317] The reactive silicone composition 11 was applied on a glass substrate, the solvent was removed, and the film was heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-2].
[0318] [Comparative Example 1]
[0319] 4 g of the mixed solution containing the reactive organosilicon compound prepared in Production Example 1 was dissolved in 5.7 g of cyclohexanone and 0.3 g of methanol to obtain a colorless and transparent comparative composition 1. The test described in (1) above was performed on the obtained comparative composition 1. The evaluation results are shown in Table 1 [Table 1-2].
[0320] Except that the rotation speed of the spin coater when applying the comparative composition 1 on the glass substrate was 500 rpm, desolvation and ultraviolet irradiation were performed in the same manner as described in Example 1 to prepare a cured film and evaluate the obtained evaluation results. Table 1 [Table 1-2] shows.
[0321] [Comparative Example 2]
[0322] 1.5 g of the mixed solution containing the reactive organosilicon compound prepared in Preparation Example 1 was dissolved in 3.5 g of 2-butanone, and 5 g of the titanium oxide colloidal particle dispersion 7 prepared in Preparation Example 8 was added thereto and mixed to obtain a light yellow transparent comparative example composition 2. The mixing amount of the core particles containing titanium oxide (in terms of all metal oxides) relative to the mass of the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, the reactive diluent, and the initiator) was 100 phr. The test shown in (1) above was performed on the obtained comparative example composition 2. The evaluation results are shown in Table 1 [Table 1-2].
[0323] This comparative composition 2 was applied, desolvated, and heated in the same manner as in Example 6 to prepare a cured film, which was then evaluated. The obtained evaluation results are shown in Table 1 [Table 1-2].
[0324] [Table 1]
[0325] Table 1-1
[0326]
[0327] ※The amount of each particle (converted to total metal oxide) mixed with the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, reactive diluent, and initiator)
[0328] Table 1-2
[0329]
[0330] ※The amount of each particle (converted to total metal oxide) mixed with the mixed solution containing the reactive organosilicon compound (the total mass of the reactive organosilicon compound, reactive diluent, and initiator)
[0331] [Evaluation results]
[0332] As shown in Table 1 (Table 1-1, Table 1-2), it was confirmed that the reactive silicone compositions 1 to 11 prepared and used in Examples 1 to 13 had higher storage stability than the comparative composition 2 prepared and used in Comparative Example 2. In addition, it was confirmed that the cured films prepared in Examples 1 to 13 showed high transmittance in the infrared region, low haze value, maintained high transparency, and excellent light resistance. It was further confirmed that the cured films prepared in Examples 1 to 13 showed a higher refractive index than that of Comparative Example 1, and the refractive index was increased by mixing and modifying the oxide colloidal particles containing titanium oxide, and the refractive index was changed by modifying the mixing amount of the oxide colloidal particles containing titanium oxide, and the refractive index could be adjusted.
Claims
1. A reactive silicone composition comprising the following components (S) and (T), The component (S) is a reactive organic silicon compound consisting of a condensation product of a diarylsilicic acid compound represented by formula [1] and a silicon compound represented by formula [2]. In the formula, Ar 1 and Ar 2 Each independently represents a phenyl group which may optionally have an alkyl group having 1 to 6 carbon atoms as a substituent, and X represents a hydrolyzable reactive group; The component (T) is a modified titanium oxide-containing colloid particle formed by bonding an organic silicon compound to the surface of a titanium oxide-containing oxide colloid particle (C) having an average particle size of 2 to 100 nm, wherein the titanium oxide-containing oxide colloid particle (C) has a titanium oxide-containing metal oxide colloid particle (A) having an average primary particle size of 2 to 60 nm as a core, and the core surface is coated with a coating formed of a composite oxide containing silicon dioxide and tin oxide and having an average primary particle size of 1 to 4 nm. The organic silicon compound bonded to the surface of the titanium oxide-containing oxide colloidal particles (C) is a silane coupling agent or at least one of the compounds represented by the following general formulas (1) to (4), General formula (1): R 2 3SiX 2 The monofunctional silane shown General formula (2): R 2 2SiX 2 2 shows the difunctional silane General formula (3): R 2 SiX 2 3 shown as trifunctional silane General formula (4): SiX 2 The tetrafunctional silane shown in 4 In the above formulas (1) to (4), R 2 represents an organic group having an alkyl group having 1 to 8 carbon atoms, a phenyl group, a vinyl group, a methacryloxy group, a mercapto group, an amino group or an epoxy group, X 2 represents a hydrolyzable reactive group, The titanium oxide content of the titanium oxide-containing metal oxide colloidal particles (A) is 50 to 100% by mass in terms of TiO2. In the colloidal particles (B), the mass ratio of silicon dioxide (SiO2) to tin oxide (SnO2) is SiO2 / SnO2=0.1 to 5.0, The modified titanium oxide-containing oxide colloidal particles of the component (T) are contained in an amount of 25 to 400 parts by mass based on 100 parts by mass of the reactive organosilicon compound of the component (S). 2 . The reactive organic silicon composition according to claim 1 , wherein the silane coupling agent is 3-[methoxy-poly(ethyleneoxy)propyl]trimethoxysilane. 3 . The reactive silicone composition according to claim 1 , comprising cyclohexanone or 2-butanone as a solvent. 4 . The reactive silicone composition according to claim 1 , further comprising a polymerization initiator. 5 . A cured product formed from the reactive silicone composition according to claim 1 . 6 . An optical adhesive, which is formed from the reactive silicone composition according to claim 1 and is used for a connection between optical waveguides or between an optical waveguide and a light receiving element in an optical signal transmission device.
7. A core member in a device for transmitting an optical signal, the core member being formed from the cured product according to claim 5. 8 . A film-forming agent formed from the reactive silicone composition according to claim 1 . 9 . An optical member comprising a cured film formed from the reactive silicone composition according to claim 1 on a surface of an optical substrate.
10. An optical component, characterized in that: The optical member according to claim 9 further has an antireflection film applied on its surface.
Citation Information
Patent Citations
Optical part of synthetic resin having reflection preventing film
JP1981116003A
Antireflection plastic lens having high refractive index
JP1990262104A
Optical adhesive and optical part using same
JP1999061081A
Adamantane derivative, reaction product thereof, curable resin composition containing the same, method for producing them and use
JP2010132576A
Polymerizable compositions, cured products obtained therefrom, and the use of these materials
JP2014510159A